The relationship between symptoms of attention-deficit/hyperactivity disorder and risk taking behaviours in adolescents - Makwela, Morongwa Caroline (My University, 2008)
Background: Attention Deficit Hyperactivity Disorders (ADHD) is a common neurodevelopmental behavioural disorder among school–age children, which in most cases continues into adolescence and adulthood and is mainly characterized by inattentiveness, hyperactivity and impulsiveness. The aim of the study was to establish the relationship between ADHD symptoms and risk taking behaviours (safety, alcohol use, tobacco use, dagga use, drug use, and sexual activity) in adolescents. Method: A total of 100 male participants (without a clinical diagnosis) participated in the study. The participants were assessed on a battery consisting of the BSSA (Barkley‟s Symptoms Scale for Adolescents), YRBS (Youth Risk Behaviour Scale) and neuropsychological tests which measure response inhibition (GoStop Task) and executive function (Wisconsin Card Sorting Test). The ADHD scores on BSSA have been correlated with scores on the YRBS as well as with the scores obtained on the WCST and the Go-Stop Task. The results were analysed using the Pearson-r to show a relationship between ADHD symptoms and risk taking behaviours. Result:: Conclusion: There is a significant although weak relationship between ADHD symptoms and most risk taking behaviours in a population of non- impaired adolescents.
Theses (M.A.) (Clinical Psychology) --University of Limpopo, 2008
Keywords: Attention deficit disorders; Hyperactivity; 155.518; Attention deficit disorders - South Africa; Hyperactive child syndrome - South Africa